JURNAL IJSW VOL 7 NO 1 2023: PARTISIPASI DAN PERSEPSI MASYARAKAT TERHADAP PROGRAM KERJA BUMDES SAUYUNAN, DI DESA CINANGSI, KECAMATAN CIBOGO, KABUPATEN SUBANG - Muhammad Ananta Firdaus; Ellya Susilowati; Fitriani Nur Halimah; Rian Dani (Politeknik Kesejahteraan Sosial Bandung, 2023)
This study aims to provide an overview of the evidence in line with whether or not community participation and perceptions of the Sauyunan BUMDes work program in Cinangsi Village, Cibogo District, Regency. This research approach is descriptive and quantitative. According to the research, the medium category dominated community participation in the Sauyunan BUMDes work program in terms of involvement in the planning process (44.4%) and involvement in the implementation process (44.7%). Additionally, it emerged from the research that the medium category of the attitude indicator (33.6%), expectations (31.7%), motivation (35.4%), perceived object (34.1%), work program facilities (35.9%), and work program atmosphere (38.9%) dominated people's perceptions of work programs. Even though the moderate category dominates for all indicators of the variables, the less category also exists in each indicator with a number that can also be considered not small and sufficient to approach the value of the number of moderate categories in each indicator. Such a state of perception and participation shows a parallel between this perception and participation and the condition of BUMDes, which experience much underdevelopment starting from dim management, vacuum, and stagnation in the types of BUMDes businesses and not supporting facilities and atmosphere. Further, it can be concluded that H0: